The Use of Translation to Facilitate the Learning of Low Frequency and Abstract English Vocabulary - Mahpar, Erlina Melati (2007)
The aim of this study is to analyse the facilitative effect of integrating selective translation in the teaching and learning of low frequency and abstract English vocabulary on below advanced proficiency students. Consequently, the objectives are to find out whether using translation and using only English are facilitative in learning English as a second language, and which of the two methods is more facilitative. Despite having been questioned and dismissed largely based on beliefs and opinions after the Grammar Translation Method era, the method has witnessed its revival in this era of Communicative Approach (Alias and Norasmadi, 2003). In general, language teachers find translation to be an extremely valuable teaching device which is a great loss should it not be exploited, especially when tortuous explanations of lexical items in the target language fail to secure students’ comprehension (Fatimah, 2001). Thus, resorting to translation is inevitably an option to ensure or enhance students’ learnability, which is the ultimate goal of this profession (Hammond, 1990). Incidentally, the long overestimated notion that the native or first language would hinder the learning of a second language should only be applied when translation is used en masse in class, not selectively and constructively. Giving honour to such extremity would only jeopardise our purpose as teachers and is, sadly, self-defeating (Wilss, 1981). Although, the taboo of using translation in English classes has been widely put into practice in Malaysia, unfortunately, our students’ proficiency is still inadequate (Abdul Hamid and Mohmadisa, 2003). The Ministry of Education could not fail to notice this. Thus, measures are taken to rectify the situation such as implementing English in the teaching of Mathematics and Science in January 2003. Several topics in Form one syllabus, prepared under the Bestari Programme, were even abolished to accommodate this implementation (Hasuria, 2003). However, what can we do for the English classes themselves? This is where translation is significant. Translation is a one of the teaching methods that is often applied on second language learners to facilitate learning. However, some resist it largely based on beliefs and opinions that translation would impede the learning of a second language. Hence, this study was initiated to provide an insight as to whether such beliefs and opinions are well-founded or are misleading. This was done through a quantitative study which is more genuine and valid than mere beliefs and opinions. The focus of this study is translation of lexical items (content words)rather than structural and grammatical words (function words). This is because the basis of learning a language is learning vocabulary (Wallace, 1982). Furthermore, a message which omits function words usually can remain comprehensible (Stubbs, 2001) while it is impossible to comprehend those which omits content words. The study concentrates on low frequency vocabulary (Thorndike and Lorge, 1959) and abstract vocabulary (Carroll, 1994) as it poses difficulty in learning. Thus, translation is applied on learners to facilitate the learning of these difficult words. Consequently, the researcher had conducted an experiment on below advanced proficiency students of Sekolah Menengah Bandar Baru Seri Petaling, Kuala Lumpur to gauge the facilitative effect of using translation in class. Two sets of post-tests were taken by the students are compared against one another and analysed by applying T-test, means and eta squared. Firstly, the facilitative effect of using translation in second language classrooms is measured. Then, the researcher evaluated whether using English solely in classrooms facilitates second language learning. Finally, both methods are compared and analysed to ascertain which method is more facilitative. The results of the study indicate that both methods (translation and English solely) facilitate second language learning. However, using translation is found to be more facilitative than using English only. Not only is it measured to be effective but largely effective in learning English as a second language. In brief, the results of this study reflect the facilitative effect of this once popular method. Thus, the resurgence of interest in the translation method nowadays may prove as a blessing.